Competency-Based Education in Multicultural Classrooms: Designing Culturally Responsive Teaching Strategies - Prihartanto, Adrianus; Padua, Shirley A; S Sicat, Alvin; Simanjuntak, Rosmerry; Sutrisman, Henny (Journal Emerging Technologies in Education, 2025)
Culturally diverse classrooms are increasingly the norm in many education systems worldwide, presenting both opportunities and challenges for equitable teaching and learning. Competency-Based Education (CBE), which emphasizes mastery of skills over time spent in instruction, holds significant promise in addressing student diversity. However, without culturally responsive strategies, CBE may fall short in meeting the learning needs of students from varied cultural and linguistic backgrounds. This study aims to explore how culturally responsive pedagogy can be effectively integrated into the design of CBE frameworks in multicultural secondary school classrooms. The research employed a qualitative design using a multiple case study approach across three multicultural urban schools. Data were collected through classroom observations, teacher interviews, and analysis of instructional materials. Thematic analysis was used to identify effective culturally responsive strategies that aligned with core CBE principles. Findings revealed that successful integration involved differentiated assessment models, contextualized learning tasks, and inclusive curriculum design that reflected students’ cultural identities. Teachers who employed these strategies observed increased learner engagement, self-regulation, and performance. The study concludes that aligning CBE with culturally responsive teaching enhances its effectiveness in multicultural settings. It recommends embedding cultural relevance as a core component in CBE-based teacher training and curriculum development.